(3YbO GdLhGgQ hGdOQQ aj CNHGQ GdbQf GdMGOi YTQs - (3eMeO Hf CHj HcQ Hf CMeO GdMSjfj GdTdj GdNVQej, HGYdhj, LeGd GdOjf,J (B1093 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTGA GdehLhOGJ HHGgQ bOQJg LeYJ eG GJab di cJGHg hXgQ ef CNHGQ gPG GdbQf GdMGOi YTQ s
(3QJH GdJQGLe Ydi GdSfhGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B338 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B215 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg hPNjQg YHOGdSdGe HLGeYI YdjcQg HGdgfO s
Keywords: (3GdJGQjNs